2007
DOI: 10.14198/ingeo2007.44.04
|View full text |Cite
|
Sign up to set email alerts
|

Criterios para contemplar la conectividad del paisaje en la planificación territorial y sectorial

Abstract: Los procesos de fragmentación de hábitats son apuntados por la comunidad científi ca como una de las principales causas de la crisis global de biodiversidad. La conectividad ecológica, o capacidad del territorio para dar soporte a los desplazamientos de las especies entre las teselas con recursos, se torna como un criterio a incorporar con urgencia en la planifi cación territorial y sectorial. Mediante una revisión de estudios en el contexto internacional, se derivan criterios para el mantenimiento y la restau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…These structures maintain landscape connectivity and strengthen permeability by allowing animal circulation. However, it is essential that such structures have particular characteristics such as the presence of dry margins underneath that allow animal circulation [59][60][61][62]. The results obtained in this study suggest that most of the bridges or sewers found in the study area did not have a dry section that allowed fauna to cross underneath.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These structures maintain landscape connectivity and strengthen permeability by allowing animal circulation. However, it is essential that such structures have particular characteristics such as the presence of dry margins underneath that allow animal circulation [59][60][61][62]. The results obtained in this study suggest that most of the bridges or sewers found in the study area did not have a dry section that allowed fauna to cross underneath.…”
Section: Discussionmentioning
confidence: 84%
“…This indicates that the greater the number of bridges, the greater the probability of roadkill. Several studies highlight the importance of bridges and sewers as potential wildlife passageways [59][60][61][62]. These structures maintain landscape connectivity and strengthen permeability by allowing animal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…A partir de los hallazgos del presente estudio, es razonable proponer que las zonas ribereñas constituyan también rutas oficiales de conectividad y de esa manera aumentar la probabilidad de que las áreas silvestres protegidas involucradas se mantengan comunicadas. Otros autores ya han destacado el valor de estas zonas como rutas de conectividad (Gurrutxaga & Lozano, 2007;García & Abad, 2014). Sin embargo, los resultados obtenidos también develan la necesidad de recuperar la conectividad estructural en determinados sectores tanto de la ruta oficial como de las zonas ribereñas.…”
Section: Discussionunclassified
“…Hence, the definition and application of connectivity criteria is one of the most powerful tools used for nature conservation. In this sense, and following Gurrutxaga and Lozano [4], the capacity of the land to allow the displacement of organisms between land patches with resources is called structural connectivity. Ecological corridors make this connectivity possible and should be considered as an essential resource in the evaluation of biodiversity and biological conservation [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MSPA connectivity analysis considers the network components and the node/connector analysis through indexes that reveal information on the functional connectivity of the territory. This functional connectivity can be defined as "the land's ability of the land to allow the movement of organisms among patches with resources" [4]. Through connectivity analysis and fragmentation of grasslands, it is possible to define their conservation status [22] as well as contribute to their survival [23]; where the spatial resolution of the mapping information used as a basis is extremely important as it can influence the results of MSPA analysis and the PC index [24].…”
Section: Introductionmentioning
confidence: 99%